Urgensi Indonesia Meratifikasi Konvensi UNESCO 1970 Dan Konvensi UNIDROIT 1995 Dalam Rangka Perlindungan Cagar Budaya di Indonesia - Surya, Evelyn; Deliana HZ, Evi; Jayakusuma, Zulfikar (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2025)
The presence of cultural heritage artifacts is crucial as they represent a nation's history and identity. Currently, the condition of cultural heritage protection in Indonesia is concerning. There have been several cases of theft of cultural heritage artifacts, including incidents within museums, which should be the safest places for such collections. An example is the case at the National Museum in Central Jakarta. According to Johannes Marbun, Coordinator of the Cultural Heritage Advocacy Society, the first case occurred in 1960 when a collection of gold and gems was stolen, followed by incidents in 1979 involving the theft of coin collections and ceramics. The fourth case happened in 1996 with the theft of paintings by Basoeki Abdullah, Raden Saleh, and Affandi, and the fifth case in 2013 involved the disappearance of four gold-plated cultural heritage artifacts. It is suspected that these historical artifacts, believed to be remnants of the ancient Mataram Kingdom and valued at billions of rupiah, are now outside the country. Therefore, the objective of this thesis research is twofold: first, to compare the regulations of the UNESCO 1970 Convention and the UNIDROIT 1995 Convention with Indonesia's Law No. 11 of 2010 concerning Cultural Heritage, and second, to emphasize the urgency of ratifying the UNESCO 1970 Convention and the UNIDROIT 1995 Convention for the protection of cultural heritage in Indonesia. This research is classified as normative research, utilizing secondary data sources and the library research technique for data collection. From the research findings, three main conclusions can be drawn. First, the condition of cultural heritage protection in Indonesia remains concerning, as evidenced by a series of theft and illegal trafficking cases. Second, Indonesia's Cultural Heritage Law, the UNESCO 1970 Convention, and the UNIDROIT 1995 Convention all aim to protect cultural heritage, but with different approaches and mechanisms. The Cultural Heritage Law focuses more on the national context and implementation through government institutions and community participation, while the UNESCO 1970 Convention and UNIDROIT 1995 Convention emphasize international cooperation and the return of illegally exported cultural artifacts. Third, the Indonesian government needs to take concrete steps to address this issue. One proposed step is to ratify the UNESCO 1970 Convention and the UNIDROIT 1995 Convention. The author's recommendations are, first, for the government to strengthen the legal framework related to cultural heritage protection by revising existing laws, and second, for Indonesia to promptly ratify the UNESCO 1970 Convention and the UNIDROIT 1995 Convention to enhance international cooperation.